Survey the Impact of Exchange rate Fluctuations on Financial Performance Indicators of Banks listed in the Tehran Stock Exchange - SeyedeMahboubeh Hoseyni; Gholamreza Zamanian; Mohammad Mirbagherijam (پژوهش‌های مدیریت عمومی, 2016)
This study evaluate the impact of exchange rate fluctuations on some important indicators of the financial performance of banks listed in the Tehran Stock Exchange. The methodology adopted in this research is descriptive-causal; library tools have been used for data collection and based on data analysis conducted through econometric techniques including ARIMA, ARCH and PANEL-VAR on the banking system sample during 1385-1394 (Persian solar calendar), this paper concludes that consistent with prevailing literature, exchange rate fluctuations have a significant and negative impact on the level of short and long-term deposits, significant and positive impact on non-performing loans; but inconsistent with reviewed literature, have a significant negative impact on net-profit and assets of banks.